MENGKRITISI KEBIJAKAN GEREJA LOKAL KEUSKUPAN RUTENG DALAM MENYIKAPI DAMPAK COVID-19 TERHADAP PELAYANAN PASTORAL - Servitia D.B Wandut; Imakulata Murni; Dariana Amul (Unit Penelitian dan Pengabdian kepada Masyarakat (UPPM), STP-IPI Malang., 2022)
This article is focused on criticizing various policies of the Diocese of Ruteng in responding to the impact of Covid-19 on pastoral care. The main issue discussed was what kind of policies were in responding to the impact of the Covid-19 pandemic on the pastoral care of the faithful. What positive things have been produced so far and what things need to be considered for improvement in the future? By using a literature review as a method as well as a document study, the author finds that at the policy level, there are various pastoral instructions issued, both regarding restrictions on pastoral care and related to charitable social action. These various policies have made a positive contribution to the faithful even though there are still things that need to be considered for improvement in the future. The author concludes that a policy like this must be seen as part of the commitment and pastoral responsibility of the Local Church of Ruteng for the good of the faithful who are affected by Covid-19 as well as a manifestation of universal humanitarian solidarity in breaking the chain of this deadly virus.